The relationship between strength, power and sprint performance in codes of rugby at a professional and semi-professional level and implications for training. - Erichsen, E. E. (Journal of Australian Strength and Conditioning, 2020)
Strength, power and sprint performance are important aspects of rugby league and union and are discriminators between levels of play and also associated with effective playing performance. The purpose of this review was to investigate the relationship between strength, power and sprint performance. The review also looked to determine the most effective methods of training sprint performance in rugby league and rugby union at a professional and semiprofessional level. A literature search was conducted using SportDiscus, Google Scholar and the Edith Cowan University database using keywords. Eighteen studies are included in this review. From the collective results of the studies included in this review, a number of conclusions can be made. Strength is significantly related to sprint performance particularly over the initial acceleration phase up to 10m, and there is a transfer of training effect between strength and sprint performance over distances up to 40m. Power is significantly related to sprint performance in distances up to 40m, and may be more related as the distance increases due to the increased involvement of the stretch shortening cycle. Furthermore, resisted sprint training is no more beneficial than non-resisted sprint training. Post-activation potentiation is beneficial for increasing sprint performance, however due to the best results being 8 minutes after the pre-load stimulus, this may not be a time efficient method. Coaches and strength and conditioning professionals should consider strength and power to improve sprint performance and should aim to seamlessly fit these aspects in to periodised training plans.